Fostering Environmental Literacy through Innovative Learning: Using PBL-based Science E-books Integrated with Local Potential of Rawa Bento - fahlevi, aditya; Jumadi, Jumadi; Wilujeng, Insih; Titisari, Galuh (Journal of Innovative Physics Teaching, 2024)
Students' poor environmental literacy is a problem that has to be fixed. This research is important because low environmental literacy among students can negatively impact their ability to understand and address environmental issues in the future. This study looked at how students' environmental literacy levels changed after using the PBL-based Rawa Bento integrated science e-book in learning. This study aims to evaluate the effect of using PBL-based Rawa Bento integrated science e-books on students' environmental literacy. This study involved grade VII students at SMPN 6 Yogyakarta with a quasi-experimental design. There are two research groups: the modeling group and the implementation group. Both groups received science learning using the PBL-based Rawa Bento integrated science e-book. Multiple-choice exams were used to collect data on environmental literacy, which SPSS 21 was then used to analyze. The results showed that in the modeling group, before and after learning, there was no discernible difference in environmental literacy. However, in the implementation group, there were significant differences and the size of the effect was moderate.